EVALUASI SISTEM AKUNTANSI PEMBELIAN DAN PENGELUARAN KAS UNTUK MENDUKUNG PENGENDALIAN INTERN (Studi Pada PT. INKA (Persero) Madiun ) - Fitra Kusuma Ningroom (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
Purchasing activities required to fulfill the the needs of companies. In purchase activity is associated with the activities of cash expenditures, the cash is used to pay for goods that have been purchased by the company to the vendor. Purchasing activities and cash expenditures must be made in appropriate good system is the system of purchase accounting and cash expenditures. Good accounting system will be provide a guarantee for the implementation of adequate internal control system in order to achieve company goals. The purpose of this study is to investigate the implementation of the purchasing accounting system and cash expenditure are applied to PT. Industri Kereta Api (Persero) Madiun and knowing whether both systems are able to support the internal control system. The results of this research is in the application of purchase accounting systems and cash expenditures on PT. Industri Kereta Api (Persero) Madiun is good enough, but there are a few weaknesses in the internal control system. In the system of authorization and recordkeeping procedures re-examination of the invoice is not done by the purchasing department. On a good practice any form that is have not print checks numbered, invoices from suppliers is not saved by the due date, as well as the basic document and supporting documents have not been stamped